Analisis Persaingan Tarif antara Telkomsel dan Indosat di Industri Telekomunikasi - Devi Melisa Damiri (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
Established Law No. 5 of 1999 on the prohibition of monopolistic practices and unfair business competition can not be separated from IMF pressure on the Indonesian government on the government to combat monopolistic practices and unfair business competition that occurred in Indonesia by immediately enacting the legislation. The purpose of this study is analyzing the telecommunications industry price war that occurs between the Telkomsel operator and Indosat Ooredoo against unfair competition. The method used in this research is descriptive method of analysis. Data used are secondary data. Results of analysis showed that Indosat Ooredoo trying to overthrow the corporate image Telkomsel in their campaign fare Rp. 1,0 and Telkomsel operator also negotiate interconnection prices unfair to Indosat Ooredoo. Keywords: Unfair Competition, Monopolistic, Telecommunications Industry